Psikoedukasi: Mewujudkan Relasi Romantis Sehat Bahagia Bagi Remaja Perempuan di Desa Pasirtanjung - Kusumawardhani, Sri Juwita; Sy, Vinna Ramadhany; Medellu, Gita Irianda Rizkyani (Universitas Negeri Jakarta, 2024)
Pasirtanjung Village residents tend to have a positive attitude towards getting married at a very young age. However, being at a young age is often accompanied by a low level of education, minimal income, and emotional immaturity, making it vulnerable to triggering conflict in marriage. Therefore, this community service program aims to provide psychoeducation to create healthy, happy relationships to minimize negative impacts on individuals, couples, and families. The main target of this program is unmarried adolescent girls aged 13-19 years. The implementation method refers to the results of the Healthy Relationship Series program, which explains that the psychoeducation program related to healthy romantic relationships has an impact on participants' in-depth understanding, especially regarding setting boundaries, communication, conflict resolution, as well as discussing additional issues such as mental health and gender-based violence. Based on the pre-test and post-test evaluation results, the average post-test score increases, concluding that the psychoeducation carried out effectively provides understanding regarding healthy, happy relationships.